Contemporary computing for engineers and scientists with Fortran 77 - McCracken, Daniel D. (New York : John Wiley, 1984)
Getting started in computing and Fortran; The assignment statement and related matters; Control structures; Subprograms; Program development and testing; Formatted input and output; The do statement and arrays; Double precision, complex, logical, and character variables; Subprograms; Nonprocedural approaches to application development.
Includes index.
Keywords: Computer program language; FORTRAN 77.; Engineering -- Data processing; Science -- Data processing; FORTRAN (Computer program language)